2018
DOI: 10.1016/j.conbuildmat.2018.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Bond behaviour of steel plate reinforced concrete beams

Abstract: This technical note presents an experimental study on the bond behaviour of chequer steel plate reinforcements in concrete members based on the beam-end method. The effects of lozenges of the chequer steel plate, the use of steel bolts, and the thickness of the concrete cover on the bond behaviour are investigated. The experimental program includes five specimens designed as beam-end pullout members. Each specimen is 225 mmwide, 300 mmhigh and 600 mmlong. Stirrups with 80 mmcentre-tocentre spacing are used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Then, the experimental study on reinforcement of damaged concrete beams with bonded steel plates was carried out under unloading and non-unloading conditions, respectively, and the bearing capacity was compared and analyzed. Although many scholars have done many works (Luo et al, 2020;Thamrin and Sari, 2017;Sarhan et al, 2018) in strengthening concrete beams with steel plates and gained rich research results, the contribution of pavement layer to bearing capacity has not been reported, which results in underestimation of the bearing capacity of the beam in-service. Therefore, this paper carried out experimental research on three hollow slab beams being used for 30 years with/without pavement layer.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the experimental study on reinforcement of damaged concrete beams with bonded steel plates was carried out under unloading and non-unloading conditions, respectively, and the bearing capacity was compared and analyzed. Although many scholars have done many works (Luo et al, 2020;Thamrin and Sari, 2017;Sarhan et al, 2018) in strengthening concrete beams with steel plates and gained rich research results, the contribution of pavement layer to bearing capacity has not been reported, which results in underestimation of the bearing capacity of the beam in-service. Therefore, this paper carried out experimental research on three hollow slab beams being used for 30 years with/without pavement layer.…”
Section: Introductionmentioning
confidence: 99%
“…Before the appearance of cracks, the chemical cementation force caused by the production of hydrated calcium silicate formed by the cement hydration reaction between the steel bar and the concrete is immersed in the surface of the steel bar. When the load of the beam reaches the cracking load, cracks will occur, and the concrete pulled between the joints will cause stress to act on the steel bars, resulting in a redistribution of the internal stress of the reinforced concrete [2][3]. The end bond of a steel bar mainly includes the end anchoring of the independent column, the anchoring of the beam end, the anchoring of the end of the cantilever beam, etc., and its function is to ensure synergy between the steel bar and the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The anchor beam test is a four-point bend with a specific anchor length and two curved cracks [20]. The splicing beam test uses a concrete beam with a known reinforced bond length and a known splicing length (the splicing length exists in the constant moment region) [2]. The whole beam test is to cast a complete beam according to the requirements of the specification, in which the length of the steel bar at the bottom is slightly longer than the beam [19].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted to examine the effect of reinforcement bar properties on the structural behavior of reinforced concrete members. To ensure the joint between reinforcement and concrete functions, however, many researchers have studied the behavior of the bond between different types of concrete and reinforcement [2]. Much of the research concluded that the bond between reinforcement and concrete can be defined as uniform shear stress over the surface of the bar, a simple and entirely inaccurate concept [3,4].…”
Section: Introductionmentioning
confidence: 99%